Геодезия; Топографические съемки: Справочное пособие - Неумывакин Ю. К. Юрий Кириллович; Халугин Е. И. Евгений Иванович; Кузнецов П. Н. Павел Никитич; Бойко А. В. Алексей Викторович; Савиных В. П. Виктор Петрович; Ященко В. Р. (Москва, Недра, 1991)
Авторы указаны на обороте титульного листа.